The Soils of Turkey (World Soils Book Series,, 2018)
This book compiles all available and relevant information concerning the soils of Turkey, including the soil survey studies conducted by universities and governmental institutes from the early 1950s until today. Recent findings and advances include the description and analyses of new profiles from some parts of the country by the chapter authors; reflecting the latest version of the World Reference Base (WRB) soil system, they produce a refined soil map. The book offers valuable guidance on soil management for planners of agricultural strategies, land management experts concerned with terrestrial carbon management (soil-sequestered and biomass carbon) and climate change mitigation, and educators concerned with raising awareness for the long-neglected significance of Turkey's soils.